1999
DOI: 10.1139/f99-039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solar ultraviolet radiation (280–400 nm) on the eggs and larvae of Atlantic cod (Gadus morhua)

Abstract: Abstract:In the Gulf of St. Lawrence, Canada, solar ultraviolet B radiation (UV-B, 280-320 nm) penetrates a significant percentage of the summer mixed-layer water column: organisms residing in this layer, such as the eggs of Atlantic cod (Gadus morhua), are exposed to UV-B. In outdoor exposure experiments, Atlantic cod eggs were incubated in the presence versus the absence of UV-B and (or) UV-A (320-400 nm). We tested two hypotheses: H 1 , UV-B induces mortality in Atlantic cod eggs, and H 2 , UV-A either exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
3
29
1
1
Order By: Relevance
“…Although studies have shown that the UV-A portion of the spectrum can cause oxidative damage in animal cells (McMillan et al, 2008), studies on marine animals have provided mixed results, with some studies demonstrating negative effects (Adams and Schick, 1996; Karentz et al, 2004) whereas others showed little effect at all (Béland et al, 1999;Kouwenberg et al, 1999). In the present study no significant effects due to exposure to UV-A radiation were observed.…”
Section: Discussioncontrasting
confidence: 54%
“…Although studies have shown that the UV-A portion of the spectrum can cause oxidative damage in animal cells (McMillan et al, 2008), studies on marine animals have provided mixed results, with some studies demonstrating negative effects (Adams and Schick, 1996; Karentz et al, 2004) whereas others showed little effect at all (Béland et al, 1999;Kouwenberg et al, 1999). In the present study no significant effects due to exposure to UV-A radiation were observed.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, our results only partially match those of other studies conducted under natural light with the embryos and larvae of other fishes (Charron et al 2000;Häkkinen et al 2001;, showing the specificity of the response to UVR. Béland et al (1999), for example, used an experimental design similar to ours to evaluate the impact of natural UVR on cod embryos, but they did not observe any negative effect of UV-A on survival. In our experiment, while larval survival varied clearly with both light quality and quantity, photodamage seems to vary with light quality only.…”
Section: Discussionmentioning
confidence: 99%
“…senile can thus be regarded as a potential animal indicator organism for UV in the marine environment, as various species of macroalgae -Delessaria sanguinea (Dring et al 1996); Porphyra umbilicalis and Palmaria palmata (Cordi et al 1999) -have been shown to be. That such indicators should be available for estimating damage and other effects exerted by UV on marine habitats is evident from many studies on the ways UV-B affects marine organisms (Beland et al 1999;Kouwenberg et al 1999aKouwenberg et al , 1999bMostajir et al 1999).…”
Section: Discussionmentioning
confidence: 99%